2012
DOI: 10.1021/jp305590f
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Properties of Amide Bearing Cleavable Gemini Surfactants by Small Angle Neutron Scattering and Conductivity Studies

Abstract: The micellar aggregation of different amide bearing cleavable gemini surfactants with varying methylene spacer chain length (m = 2, 4, 6, 8, and 12) along with the corresponding monomeric surfactant in aqueous media has been investigated by conductometric and small angle neutron scattering (SANS) studies. The critical micellar concentration (CMC) values of gemini surfactants were found to be very low (CMC = 0.08-0.19 mM) and were 23-55 times lesser than the corresponding monomeric analogue (CMC = 4.4 mM). With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 60 publications
(117 reference statements)
1
42
0
Order By: Relevance
“…38,39 Following that, 2-chloro-N-dodecylacetamide was subsequently quaternized by different heterocyclic amines (N-methyl piperidine, N-methyl pyrrolidine, N-methyl imidazole and N-methyl morpholine) in the second step to get amide-functionalized SAILs. The detailed methodology of synthesis and characterization data (NMR and mass) are provided in Annexure 1 (ESI †).…”
Section: Synthesis and Thermal Stabilitymentioning
confidence: 99%
“…38,39 Following that, 2-chloro-N-dodecylacetamide was subsequently quaternized by different heterocyclic amines (N-methyl piperidine, N-methyl pyrrolidine, N-methyl imidazole and N-methyl morpholine) in the second step to get amide-functionalized SAILs. The detailed methodology of synthesis and characterization data (NMR and mass) are provided in Annexure 1 (ESI †).…”
Section: Synthesis and Thermal Stabilitymentioning
confidence: 99%
“…[39][40][41][42] The higher toxicities displayed by the amide and ester surfactants could then be the result of the breaking of the gemini molecule (at the spacer linkage) into two molecules of monomeric serine-derived surfactant, which would double the effective surfactant concentration of cationic surfactant in contact with the cells. It has been reported that surfactants with cleavable bonds (i.e., amide and ester) can easily undergo enzymatic degradation.…”
Section: Influence Of the Nature Of The Spacer Linkagesmentioning
confidence: 99%
“…10 wt%, 20 wt%, 30 wt% and 40 wt%) at 25 1C and the results of the experiments are shown in Fig. [49][50][51][52] The presence of this polar ether linkage in the morpholinium headgroup in addition to the ester group may result in the formation of hydrogen bonding between the nonbonding electrons on oxygen atoms and water molecules, which ultimately influences not only the thermodynamic behavior but also the rheological behavior of the surfactants. 48 The morpholinium gemini surfactant: [C12MOR(2Es)-C12MOR]2Br demonstrated lower viscosity compared to the other gemini surfactant solutions.…”
Section: Viscosity Of Aqueous Surfactant Solutionsmentioning
confidence: 99%